(untitled) (Al-Aasar, 2026)
Silence is often mistaken for the mere absence of meaning. Yet, in philosophy, silence is not connected to absence at all. Instead, philosophy considers silence as a rich and contested phenomenon that not only denotes the negation but also reflects the resistance and divine existence. The philosophers inquired silence and meaning by diving them into phenomenological and analytic philosophical dimensions. The phenomenological dimension of silence reveals that silence is an active force that shapes the meaning in ways a language cannot, alone (Davies, & Turner, 2002). Whereas the analytic philosophy comes up with the stance that silence is the boundary of expressions, everything that remains unsaid may still signify.